Negative Aging Self-stereotypes and Aging Perceptions beyond a Holistic Perspective - Feba John; P. V. Athiramol; Ramalingam Kameswaran; Krishnaveni Kandasamy (Archives of Medicine and Health Sciences)
The aging population is increasing, and their well-being is a critical issue worldwide. The concept of “self-perceptions of senescence” refers to how individuals view their own aging process, with successful aging characterized by good physical and cognitive functioning, absence of illness, and socialization. However, education and wealth can limit the number of successful agers. Psychological determinants, such as stress, anxiety, emotional stability, and social support, play a vital role in quality of life, while social determinants, such as access to health care, income, and social support networks, are also important factors. Age-related self-stereotypes can be acquired in two stages, as individuals become targets of age-related prejudices and stereotypes that encompass their traits, actions, skills, and desires. These commonly held beliefs, known as “old-age stereotypes,” stem from age being a prevalent social construct that affects many aspects of people’s lives.